Primary harbour seal (Phoca vitulina) airway epithelial cells show high susceptibility to infection by a seal‐derived influenza A virus (H5N8). Issue 5 (13th May 2022) - Shin, Dai‐Lun; Siebert, Ursula; Haas, Ludwig; Valentin‐Weigand, Peter; Herrler, Georg; Wu, Nai‐Huei
Abstract: Highly pathogenic avian influenza viruses of the H5N8 subtype have been circulating in Europe and Asia since 2016, causing huge economic losses to the poultry industry. A new wave of H5Nx infections has begun in 2020. The viruses mainly infect wild birds and waterfowl; from there they spread to poultry and cause diseases. Previous studies have shown that the H5N8 viruses have seldom spread to mammals; however, reports in early 2021 indicate that humans may be infected, and some incident reports indicate that H5Nx clade 2.3.4.4B virus may be transmitted to wild mammals, such as red foxes and seals. In order to get more information on how the H5N8 virus affects seals and other marine animals, here, we used primary cultures to analyze the cell tropism of the H5N8 virus, which was isolated from an infected grey seal (H5N8/Seal‐2016). Primary tracheal epithelial cells were readily infected by H5N8/Seal ‐2016 virus; in contrast, the commonly used primary seal kidney cells required the presence of exogenous trypsin to initiate virus infection. When applied to an ex vivo precision‐cut lung slice model, compared with recombinant human H3N2 virus or H9N2 LPAI virus, the H5N8/Seal‐2016 virus replicated to a high titre and caused a strong detrimental effect; with these characteristics, the virus was superior to a human H3N2 virus and to an H9N2 LPAI virus. By using well‐differentiated air–liquid interface (ALI) cultures, we have observed that ALI cultures of canines, ferrets, and harbour seals are more sensitive to H5N8/Seal‐2016 virus than are human or porcine ALI cultures, which cannot be fully explained by sialic acid distribution. Our results indicate that the airway epithelium of carnivores may be the main target of H5N8 viruses. Consideration should be given to an increased monitoring of the distribution of highly pathogenic avian influenza viruses in wild animals.